Mapping And Analysis Of Measles Cases In Children Aged 1-9 Years In Situbondo Regency In 2024 - Rizma Khaila Putri Hamdani; Lucia Yovita Hendrati (CV. AFDIFAL MAJU BERKAH, 2026)
This study aims to map and analyze measles cases in children aged 1-9 years in Situbondo Regency in 2024, based on measles immunization coverage and population density. Using a descriptive analytical method with an ecological study approach and secondary data from the 2024 East Java Health Profile, the unit of analysis was 17 sub-districts in Situbondo Regency. Spatial analysis was conducted using Health Mapper and GeoDa for Global Moran's I and Bivariate Local Indicator of Spatial Association (BiLISA). The results showed that measles immunization coverage in all sub-districts has not reached the national target of 95%, with Panji District having the highest proportion of cases. Global Moran's I analysis found a significant negative spatial autocorrelation between immunization coverage and measles cases (I = -0.330, p = 0.015), indicating that areas with high immunization coverage tend to be adjacent to areas with low cases, and vice versa. Meanwhile, for population density, no significant spatial autocorrelation was found (I = 0.217, p = 0.053), although densely populated areas tended to have a higher proportion of cases. This indicates that while immunization coverage has a clear spatial relationship with measles cases, population density is not the sole determining factor.